Palestine and Saudi Arabia, Two Different Countries with Two Different Conditions: Are the Determinants of Capital Structure of Corresponding Markets the Same? - Abu Khalaf, Bashar K.; Al-Nees, Bara; Sukkari, Lilana (International Journal of Economics and Financial Issues, 2017)
This paper investigates the determinants of capital structure of two different countries, Saudi Arabia and Palestine. The analysis employs panel data analysis and seemingly unrelated regression based on a sample of 21 listed Palestinian companies and 61 Saudi companies. The study in this paper extends from 2005 to 2015. The findings of this study indicate that the leverage ratios of both Palestinian and Saudi firms are low. Moreover, the most common determinants of capital structure are found and significantly affecting both Palestinian and Saudi firms, finally the differences in the magnitudes and sign of the coefficients are because of country-level differences and not due to firm-level differences. Keywords: capital structure, financial markets, Saudi Arabia, Palestine JEL Classifications: D53, E44, G31